Local Culture-Oriented Pop Up Book Media to Improve IPAS Learning Outcomes of Grade III Elementary School Students - Tampayana, I Putu; Sanjaya, Putu; Suparya, I Ketut (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The limited use of engaging concrete media has contributed to students’ low learning outcomes. Therefore, the aim of this study is to implement Pop-Up Book media oriented toward local culture to improve the IPAS learning outcomes of Grade III elementary school students. This research employed a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design Posttest Only, which involved two groups, namely the experimental class and the control class. The research population consisted of all Grade III students at SD Negeri Gugus VIII Mengwi. The research sample was selected through random sampling, with SD Negeri 1 Mengwi serving as the experimental class, which received the treatment of using Pop Up Book media oriented toward Balinese local culture in IPAS learning, while SDN 2 Werdi Bhuwana served as the control class, which used conventional learning without such media. The research instrument was a learning outcomes test that had been declared valid and reliable. The analysis was conducted through prerequisite tests in the form of normality and homogeneity tests, followed by hypothesis testing using the independent t-test to determine the difference in learning outcomes between the experimental and control classes. The independent t-test hypothesis test yielded a 2-tailed significance value of 0.000 < 0.05, indicating that there is a significant effect of Pop Up Book media oriented toward Balinese local culture on the IPAS learning outcomes of Grade III elementary school students. In conclusion, Pop Up Book media oriented toward Balinese local